Stylised facts and other empirical evidence on firm dynamics, business cycle and growth - Pedro Rui Mazeda Gil (2010)
In this paper, we bring together, in a systematised fashion, the scattered empirical evidence relating firm dynamics with both short-run and long-run macroeconomic dynamics. There are numerous studies that focus on firm-level data while controlling for macroeconomic conditions. From these studies a fairly robust set of empirical regularities pertaining to entry, exit, growth and the size distribution of firms has emerged. However, the literature that focuses explicitly on the interplay between firm dynamics and the business cycle is roughly confined to the US experience and to the cyclical properties of firm entry and exit, while the studies about the relationship between firm dynamics and economic growth are limited and unsystematic. We also give a brief account of the most recent theoretical literature on firm dynamics and macroeconomic dynamics, and try to relate it to the empirical findings.